GRAPHOSPHERE IN URBAN SPACE OF THE EARLY MODERN (XV – XVIII CENTURIES) IN THE DIMENSION OF ANTONIO CASTILLO GÓMEZ’S CULTURAL HISTORY - Pavlova, Olena (Ukrainian Cultural Studies, 2023)
The article explains the fundamental concepts of the graphosphere, shedding light on the organization of written communication within urban spaces during the early Modern period (15th to 18th centuries). The elucidation of these basic concepts is approached through the lens of various oppositions, such as "center-periphery" (N. Luhmann), "great-little tradition" (R. Redfield, M. Singer), "independent-subservient architecture" (G. Hegel), and "space of representations-representational spaces" (H. Lefebvre). The specificity of these cultural-historical approaches is revealed through the theoretical and empirical dimensions of studying the graphosphere, which involves differentiating between signifiers and signifieds. Therefore, examining written communication in early modern cities (15th to 18th centuries) clarifies the significance of material culture as a central theme in cultural history. This exploration goes beyond the narrow definition of textual materiality and encompasses examining the locations and methods of publication. This broader perspective expands how this topic can be conceptualized and provides an empirical foundation. Written communication practices not only influence the semantic centrality of space (although it remains closely connected to urban space) but also contribute to the transformation of textual materiality and the differentiation between public place and public space. In the early Modern period, written communication, while still connected to urban walls, gained a greater potential for re-signifying public space. This led to its appropriation through graphic colonization and illegal acts (which both indicate the democratic nature of cultural changes and increase the potential for communication conflicts). The autonomization of signifiers order establishes the superiority of representational spaces over the space of representations. The "paper wars" can be seen as the first historical form of information warfare and the beginnings of a "great tradition" of colonizing public space without physical occupation, which became a prerequisite for territorial occupation